Thorough-bread? A study of the system of provision of bread in South Africa - Van der Walt, Katharina (My University, 2016)
Over one billion people in the world are under-nourished, and over two billion suffer from malnutrition of micro-nutrients – known as ‘hidden hunger’1. This is largely due to the fact that two thirds of the world’s population depend on cereal or tuber based diets (e.g., wheat, maize, potatoes) which tend to satisfy energy demands but not essential micro-nutrients2. The industrialisation of food production systems that occurs as part of the process of economic development has been linked to great improvements in access to food on the one hand, but this has also resulted in major transitions in population-level food consumption and lifestyle patterns. The changes affecting both dietary and physical activity have been termed the ‘nutrition transition’3, which signals the change from consuming large amounts of fibre and low amounts of fat, to a diet comprised of highly processed, high-energy foods. Developing countries now face a ‘triple burden’ in terms of overcoming under-nutrition of micro and macro nutrients, as well as addressing over-consumption related to the ‘nutrition transition’ that accompanies economic development4. Given this setting, this paper sets out to understand how the industrialisation of the wheat to bread chain in South Africa has influenced population consumption patterns and to what extent consumer interests have been marginalised in the pursuit of industrial efficiencies during the development of this chain. This will be done using a ‘Systems of Provision’ approach which enables a vertical analysis of the processes leading up to consumption, whilst allowing for the incorporation of historically defined, context-specific influences on chain development and consumption patterns, including political, socio-economic and cultural factors, which other vertical approaches, such as the Global Value Chain framework do not enable.
Research report submitted to the Faculty of Commerce, Law and Management at the University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree of Master of Commerce in Development Theory and Policy.
Keywords: Bread industry--South Africa; Wheat products--South Africa; Wheat trade--Economic aspects--South Africa; Wheat--Prices--Government policy--South Africa